Departure 37 : a novel - Carson, Scott, 1982- (Emily Bestler Books/Atria, 2025)
"On a clear October day, the American skies empty after hundreds of pilots refuse to fly, triggering a complete ground stop as authorities seek to explain an act of baffling coordination that the pilots insist was anything but planned. The pilots received disturbing, middle-of-the-night calls from their mothers, and each mother had a simple and urgent request: do not fly today. There are a few concerning elements to the calls. None of the mothers remember making them--and some of the mothers are dead. While the nation's military chiefs and artificial intelligence experts mobilize in search of answers, a sixteen-year-old girl named Charlie on the coast of Maine watches a strange, silvery balloon drift across the water and toward her home--a place she loathes. Her father's dream of opening a craft brewery on an old airfield has been a disaster, and all she wants is an escape back to Brooklyn. She's about to get much more than that. Her new home is ground zero for a story that begins at a remote naval base in Indiana during the winter of 1962, when a physicist named Martin Hazelton discovered something extraordinary--and deadly. All Hazelton wanted was time to seek an explanation, but pressure from both American and Russian actors forced him into a perilous race"--